Design And Optimization Of Special Low-Level Amplifier For Measurement Of Air Ions - Zdražil, Lukáš (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2020)
This paper deals with low-current measurement in order of picoamps up to a few dozens of femtoamps. Such low currents measuring is necessary for determination of air ions concentration. Disturbances, which are otherwise negligible for ordinary measurements must be considered. For example, leakage currents and noise generated in measuring device circuit. The choice of a precise operation amplifier with low input bias current is as important as the selection of low noise passive components.
Keywords: low level measurements; air ions; aspiration condenser; electrometric amplifiers